Evolution of skull and body shape in Triturus newts reconstructed from three‐dimensional morphometric data and phylogeny. (18th June 2014) - Ivanović, Ana; Arntzen, Jan W.
<x xml:space="preserve">Abstract</x> To explore the relationship between morphological change and species diversification, we reconstructed the evolutionary changes in skull size, skull shape, and body elongation in a monophyletic group of eight species that make up salamander genus Triturus. Their well‐studied phylogenetic relationships and the marked difference in ecological preferences among five species groups makes this genus an excellent model system for the study of morphological evolution. The study involved three‐dimensional imagery of the skull and the number of trunk vertebrae, in material that represents the morphological, spatial, and molecular diversity of the genus. Morphological change largely followed the pattern of descent. The reconstruction of ancestral skull shape indicated that morphological change was mostly confined to two episodes, corresponding to the ancestral lineage that all crested newts have in common and the Triturus dobrogicus lineage. When corrected for common descent, evolution of skull shape was correlated to change in skull size. Also, skull size and shape, as well as body shape, as inferred from the number of trunk vertebrae, were correlated, indicating a marked impact of species' ecological preferences on morphological evolution, accompanied by a series of niche shifts, with the most pronounced one in the T. dobrogicus lineage. The presence of phylogenetic signal and correlated evolutionary changes in skull and body shape suggested complex interplay of niche shifts, natural selection, and constraints by a common developmental system. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 243–255.